GPRC5A Is a Negative Regulator of the Pro-Survival PI3K/Akt Signaling Pathway in Triple-Negative Breast Cancer - Yang, Lu; Zhao, Shaorong; Zhu, Tong; Zhang, Jin (Frontiers in Oncology, 2021)
Breast cancer is one of the most common types of malignancy worldwide; however, its underlying mechanisms remain unclear. In the present study, we investigated the roles of G-protein-coupled receptor family C, member 5, group A (GPRC5A) in cell apoptosis in triple-negative breast cancer (TNBC). The expression of GPRC5A in breast cancer cell lines was detected by real time PCR and western blot. And the results suggested that GPRC5A was downregulated in breast cancer cell lines compared to normal breast epithelial cell lines. Additionally, the expression of GPRC5A in TCGA database was analysed in silico. GPRC5A exhibited the lowest expression levels in TNBC compared to ER+ and HER2+ breast cancer. Overexpression of GPRC5A in MDA-MB-231 and MDA-MB-468 cells promoted apoptosis, whereas depletion of GPRC5A in T47D and MCF7 cells inhibited cell apoptosis via the intrinsic apoptotic pathway. We performed RNA-sequencing in GPRC5A overexpressed MDA-MB-231 and the control cells. The results facilitated the identification of a number of signaling pathways involved in this process, and the PI3K/Akt signaling pathway was found to be one the most important. A specific activator of the PI3K/Akt signaling pathway inhibited apoptosis of breast cancer cells, whereas cotreatment of this activator with a GPRC5A-expressing plasmid reduced this effect. Similarly, a specific inhibitor of the PI3K/Akt signaling pathway increased cell apoptosis by activating caspase-3 and caspase-9, whereas co-incubation of the inhibitor with a short hairpin RNA targeting GPRC5A significantly reduced the cell apoptotic rate. Additionally, the overexpression of GPRC5A suppressed tumor growth by inducing cell apoptosis in vivo. Taken together, the present study identified GPRC5A as a protective factor against the progression of human triple-negative breast cancer by increasing cell apoptosis via the regulation of the PI3K/Akt signaling pathway.